Monitoring Urban Sprawl in Ambon City Using Google Earth Engine: Memantau Urban Sprawl di Kota Ambon Menggunakan Mesin Google Earth - Heinrich Rakuasa; Philia Christi Latue (Institute of Educational, Research, and Community Service, 2023)
Urban sprawl is an increasing problem in many cities around the world including Ambon City. Monitoring urban sprawl is critical to understanding its impact on the environment and quality of life. This study used Landsat 4 Level 2, Collection 2, Tier 1 - Year 1990, 1995, Landsat 5 Level 2, Collection 2, Tier 1 - 2000, 2005, Landsat 7 Level 2, Collection 2, Tier 1 - 2010, Landsat 8 Level 2, Collection 2, Tier 1 - 2015 and Landsat 9 Level 2, Collection 2, Tier 1 Year 2 - Year 2020 satellite image data which were dodowloaded and analyzed on Google Earth Engine. The results showed that the area of built-up land in Ambon City from year to year experienced an increase in area. In 1990 built-up land in Ambon City was 2,772.78 ha, in 1995 built-up land had an area of 2,237.06 ha, in 2002 built-up land in Ambon City had an area of 1,503.19 ha. In 2000 built-up land in Ambon City experienced a decrease in area, as a result of the 199-1999 riots or social conflicts in Ambon City. In 2005 built-up land had an area of 2,589.57 ha, in 2010 built-up land had an area of 2,340.40 ha, in 2015 built-up land had an area of 3,993.17 ha and in 2020 built-up land continued to experience an increase in area of 4,085.54 ha. Research results enable stakeholders to make evidence-based decisions, plan urban development more efficiently, and involve communities in decision-making. With a data-driven approach and advanced technology, it is expected that cities like Ambon City can develop sustainably and harmonize urban growth with environmental sustainability and people's quality of life